2000
DOI: 10.1074/jbc.m001006200
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the Native Strain in Human α1-Antitrypsin and Its Association with Protease Inhibitor Function

Abstract: Serine protease inhibitors (serpins) are metastable in their native state. This strain, which is released upon binding to target proteases, is essential for the inhibitory activity of serpins. To understand the structural basis of the native strain, we previously characterized stabilizing mutations of ␣ 1 -antitrypsin, a prototypical inhibitory serpin, in regions such as the hydrophobic core. The present study evaluates the effects of single point mutations throughout the molecule on stability and protease inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 36 publications
3
63
0
Order By: Relevance
“…A number of studies have shown that this region is proposed to play a crucial role in establishing and maintaining serpin stability (Seo et al 2000;Tew and Bottomley 2001a). The structures described here suggested a number of residues that may be responsible for binding the citrate ion as well as identifying residues that make up the binding pocket.…”
Section: Citrate Stabilizes Aat Against Unfolding and Polymerizationmentioning
confidence: 92%
“…A number of studies have shown that this region is proposed to play a crucial role in establishing and maintaining serpin stability (Seo et al 2000;Tew and Bottomley 2001a). The structures described here suggested a number of residues that may be responsible for binding the citrate ion as well as identifying residues that make up the binding pocket.…”
Section: Citrate Stabilizes Aat Against Unfolding and Polymerizationmentioning
confidence: 92%
“…An interaction between AAT and its target enzyme results in a conformational transition of AAT that allows the opening of ␤-sheet A and insertion of the cleaved reactive site loop (45). The insertion of the reactive site strand into ␤-sheet A can also be induced under mild denaturation conditions and during intermolecular polymerization of AAT (46).…”
Section: Detection Of Various Molecular Forms Of Aat By the Mono-mentioning
confidence: 99%
“…If the increase in the stability of the native state of ␣ 1 AT is manifested in the formation of the inhibitory complex, there should be a correlation between that increase in stability and the loss of inhibitory activity. Interestingly, however, only the stabilizing substitutions in the loop insertion region, such as Lys 335 (23) and Gly 117 (18) of sheet A, decreased the inhibitory activity, and the stabilizing mutations at most other sites of ␣ 1 AT did not cause the activity loss (17). It was shown recently that cavity filling substitutions designed at several sites of ␣ 1 AT increased the stability of the molecule, but activity affecting mutations among them were localized in the region that appears to be mobilized during the loop insertion (22 1 The abbreviations used are: serpin, serine protease inhibitor; ␣ 1 AT, ␣ 1 -antitrypsin; PPE, porcine pancreatic elastase; HLE, human leukocyte elastase; SI, stoichiometry of inhibition.…”
mentioning
confidence: 99%
“…In the crystal structure of the native ␣ 1 AT (19,20), unfavorable interactions such as side chain overpacking, buried polar groups, internal cavities, and surface hydrophobic pockets occur (16,17). These unfavorable interactions can be replaced by stabilizing substitutions (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation